Recognizing the Sequences of Code Manipulated Short LFM Signals - LESZCZYŃSKI, Tadeusz (Archives of Acoustics, 2012)
Noise-like binary sequences combined with signals with linear frequency modulation might be suc- cessfully used to increase the reliability of the recognition of both probe and communication signals in the presence of natural and artificial interference. To identify such formed sequences the usage of the two-step matched filtering was suggested and the probabilistic model of the recognition of noise-like code sequences transferred by LFM signals was developed.